SEGMENTATION, TARGETING AND POSITIONING ANALYSIS BY BROADCASTING PROGRAM RADIO MITRA 97,0 FM BATU CITY - Agustim, Warter (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2016)
This research was caused by the changing environment and other supporting factors. The changing of business pattern of Seller Market to Buyer Market made a company has to adapt their need and changing behaviour. By having this base a company need to do market segmenting, targeting, and positioning with broadcast program in order to serve customers having different characteristics. This research proposed to find out Segmenting, Targeting and Positioning (STP) Application in Mitra 97.0 Fm Radio Station of Batu City in considering the marketing strategy by determining STP. This research used descriptive method reflecting the execution of STP and the shortage of the company in implementing STP. Form the analysis result done, Mitra 97.0 Fm Radio of Batu City tried to serve the large market and divide its customers (listeners) in several segmenting variables.